Pest categorisation of Pyrrhoderma noxium - EFSA Panel on Plant Health (PLH); Claude Bragard; Paula Baptista; Elisavet Chatzivassiliou; Francesco Di Serio; Paolo Gonthier; Josep Anton Jaques Miret; Annemarie Fejer Justesen; Alan MacLeod; Christer Sven Magnusson; Panagiotis Milonas; Juan A. Navas‐Cortes; et al. (EFSA Journal)
Abstract Following the commodity risk assessment of bonsai plants (Pinus parviflora grafted on Pinus thunbergii) from China performed by EFSA, the EFSA Plant Health Panel performed a pest categorisation of Pyrrhoderma noxium, a clearly defined plant pathogenic basidiomycete fungus of the order Hymenochaetales and the family Hymenochaetaceae. The pathogen is considered as opportunistic and has been reported on a wide range of hosts, mainly broad‐leaved and coniferous woody plants, causing root rots. In addition, the fungus was reported to live saprophytically on woody substrates and was isolated as an endophyte from a few plant species. This pest categorisation focuses on the hosts that are relevant for the EU (e.g. Citrus, Ficus, Pinus, Prunus, Pyrus, Quercus and Vitis vinifera). Pyrrhoderma noxium is present in Africa, Central and South America, Asia and Oceania. It has not been reported in the EU. Pyrrhoderma noxium is not included in Commission Implementing Regulation (EU) 2019/2072. Plants for planting (excluding seeds), bark and wood of host plants as well as soil and other growing media associated with plant debris are the main pathways for the entry of the pathogen into the EU. Host availability and climate suitability factors occurring in parts of the EU are favourable for the establishment and spread of the pathogen. The introduction and spread of the pathogen into the EU are expected to have an economic and environmental impact in parts of the territory where hosts are present. Phytosanitary measures are available to prevent the introduction and spread of the pathogen into the EU. Pyrrhoderma noxium satisfies all the criteria that are within the remit of EFSA to assess for this species to be regarded as potential Union quarantine pest.